Impact of Self-Assessment on Income and Sale Tax Collection' From the Point View of Income Tax Auditors in Jordan (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study aimed to show the extent of compliance with the income taxpayer  to provide tax returns and increase the speed of collection of these taxes in addition to increasing confidence in  Income Tax department and reduce the number of cases transferred to the courts and promote taxpayer awareness in charge of the importance of self-assessment system, and study sought to investigate the effect of the existence of records documents, technical audit, and computational audit and documentary audit on income tax collections in Jordan, from the point of viewof Jordanian income tax auditors ,results shows there's a strong  relation between these variables and Income Tax collections.